Neural correlates of explicit and implicit emotion processing in relation to treatment response in pediatric anxiety. (8th November 2016) - Burkhouse, Katie L.; Kujawa, Autumn; Klumpp, Heide; Fitzgerald, Kate D.; Monk, Christopher S.; Phan, K. Luan
Abstract : Background: Approximately 40%–45% of youth with anxiety disorders do not achieve remission (or a substantial reduction in symptoms) following treatment, highlighting the need to identify predictors of treatment response. Given the well‐established link between attentional biases and anxiety disorders in youth and adults, this study examined the neural correlates of directing attention toward and away from emotional faces in relation to pediatric anxiety treatment response. Method: Prior to beginning treatment with the selective serotonin reuptake inhibitor (SSRI) sertraline or cognitive behavior therapy (CBT), 37 youth (age 7–19 years) with generalized and/or social anxiety disorder completed a task with conditions that manipulated whether participants were instructed to match emotional faces (explicit emotion processing) or match shapes in the context of emotional face distractors (implicit emotion processing) during functional magnetic resonance imaging. Results: Results revealed that reduced activation in superior frontal gyrus (SFG), encompassing the dorsal anterior cingulate cortex (ACC) and dorsomedial prefrontal cortex (PFC), during implicit processing of emotional faces predicted a greater reduction in anxiety severity pre‐to‐post treatment. Post hoc analyses indicated that effects were not significantly moderated by the type of treatment or anxiety type. Conclusions: Findings suggest that less recruitment of SFG, including the dorsal ACC and dorsomedial PFC, during implicit emotion processing predicts a greater reduction in youth anxiety symptoms pre‐to‐post treatment. Youth who exhibit reduced activation in these areas while matching shapes in the context of emotional face distractors may have more to gain from CBT and SSRI treatment due to preexisting deficits in attentional control. These findings suggest that neuroimaging may be a useful tool for predicting which youth are most likely to benefit from anxiety treatment.